CX3 chemokine receptor 1 defciency leads to reduced dendritic complexity and delayed maturation of newborn neurons in the adult mouse hippocampus - Feng Xiao; Jun-mei Xu; Xing-hua Jiang (Neural Regeneration Research, 2015)
Previous studies have shown that microglia impact the proliferation and differentiation of neurons during hippocampal neurogenesis via the fractalkine/CX3 chemokine receptor 1 (CX3CR1) signaling pathway. However, whether microglia can influence the maturation and dendritic growth of newborn neurons during hippocampal neurogenesis remains unclear. In the present study, we found that the number of doublecortin-positive cells in the hippocampus was decreased, and the dendritic length and number of intersections in newborn neurons in the hippocampus were reduced in transgenic adult mice with CX3CR1 deficiency (CX3CR1GFP/GFP). Furthermore, after experimental seizures were induced with kainic acid in these CX3CR1-deficient mice, the expression of c-fos, a marker of neuronal activity, was reduced compared with wild-type mice. Collectively, the experimental findings indicate that the functional maturation of newborn neurons during hippocampal neurogenesis in adult mice is delayed by CX3CR1 deficiency.